Datasets:
Tasks:
Text Generation
Modalities:
Text
Sub-tasks:
language-modeling
Languages:
English
Size:
100K - 1M
License:
/- | |
Copyright (c) 2020 Kevin Kappelmann. All rights reserved. | |
Released under Apache 2.0 license as described in the file LICENSE. | |
Authors: Kevin Kappelmann | |
-/ | |
import algebra.continued_fractions.continuants_recurrence | |
import algebra.continued_fractions.terminated_stable | |
import tactic.linarith | |
import tactic.field_simp | |
/-! | |
# Equivalence of Recursive and Direct Computations of `gcf` Convergents | |
## Summary | |
We show the equivalence of two computations of convergents (recurrence relation (`convergents`) vs. | |
direct evaluation (`convergents'`)) for `gcf`s on linear ordered fields. We follow the proof from | |
[hardy2008introduction], Chapter 10. Here's a sketch: | |
Let `c` be a continued fraction `[h; (a₀, b₀), (a₁, b₁), (a₂, b₂),...]`, visually: | |
a₀ | |
h + --------------------------- | |
a₁ | |
b₀ + -------------------- | |
a₂ | |
b₁ + -------------- | |
a₃ | |
b₂ + -------- | |
b₃ + ... | |
One can compute the convergents of `c` in two ways: | |
1. Directly evaluating the fraction described by `c` up to a given `n` (`convergents'`) | |
2. Using the recurrence (`convergents`): | |
- `A₋₁ = 1, A₀ = h, Aₙ = bₙ₋₁ * Aₙ₋₁ + aₙ₋₁ * Aₙ₋₂`, and | |
- `B₋₁ = 0, B₀ = 1, Bₙ = bₙ₋₁ * Bₙ₋₁ + aₙ₋₁ * Bₙ₋₂`. | |
To show the equivalence of the computations in the main theorem of this file | |
`convergents_eq_convergents'`, we proceed by induction. The case `n = 0` is trivial. | |
For `n + 1`, we first "squash" the `n + 1`th position of `c` into the `n`th position to obtain | |
another continued fraction | |
`c' := [h; (a₀, b₀),..., (aₙ-₁, bₙ-₁), (aₙ, bₙ + aₙ₊₁ / bₙ₊₁), (aₙ₊₁, bₙ₊₁),...]`. | |
This squashing process is formalised in section `squash`. Note that directly evaluating `c` up to | |
position `n + 1` is equal to evaluating `c'` up to `n`. This is shown in lemma | |
`succ_nth_convergent'_eq_squash_gcf_nth_convergent'`. | |
By the inductive hypothesis, the two computations for the `n`th convergent of `c` coincide. | |
So all that is left to show is that the recurrence relation for `c` at `n + 1` and and `c'` at | |
`n` coincide. This can be shown by another induction. | |
The corresponding lemma in this file is `succ_nth_convergent_eq_squash_gcf_nth_convergent`. | |
## Main Theorems | |
- `generalized_continued_fraction.convergents_eq_convergents'` shows the equivalence under a strict | |
positivity restriction on the sequence. | |
- `continued_fractions.convergents_eq_convergents'` shows the equivalence for (regular) continued | |
fractions. | |
## References | |
- https://en.wikipedia.org/wiki/Generalized_continued_fraction | |
- [*Hardy, GH and Wright, EM and Heath-Brown, Roger and Silverman, Joseph*][hardy2008introduction] | |
## Tags | |
fractions, recurrence, equivalence | |
-/ | |
variables {K : Type*} {n : ℕ} | |
namespace generalized_continued_fraction | |
variables {g : generalized_continued_fraction K} {s : seq $ pair K} | |
section squash | |
/-! | |
We will show the equivalence of the computations by induction. To make the induction work, we need | |
to be able to *squash* the nth and (n + 1)th value of a sequence. This squashing itself and the | |
lemmas about it are not very interesting. As a reader, you hence might want to skip this section. | |
-/ | |
section with_division_ring | |
variable [division_ring K] | |
/-- | |
Given a sequence of gcf.pairs `s = [(a₀, bₒ), (a₁, b₁), ...]`, `squash_seq s n` | |
combines `⟨aₙ, bₙ⟩` and `⟨aₙ₊₁, bₙ₊₁⟩` at position `n` to `⟨aₙ, bₙ + aₙ₊₁ / bₙ₊₁⟩`. For example, | |
`squash_seq s 0 = [(a₀, bₒ + a₁ / b₁), (a₁, b₁),...]`. | |
If `s.terminated_at (n + 1)`, then `squash_seq s n = s`. | |
-/ | |
def squash_seq (s : seq $ pair K) (n : ℕ) : seq (pair K) := | |
match prod.mk (s.nth n) (s.nth (n + 1)) with | |
| ⟨some gp_n, some gp_succ_n⟩ := seq.nats.zip_with | |
-- return the squashed value at position `n`; otherwise, do nothing. | |
(λ n' gp, if n' = n then ⟨gp_n.a, gp_n.b + gp_succ_n.a / gp_succ_n.b⟩ else gp) s | |
| _ := s | |
end | |
/-! We now prove some simple lemmas about the squashed sequence -/ | |
/-- If the sequence already terminated at position `n + 1`, nothing gets squashed. -/ | |
lemma squash_seq_eq_self_of_terminated (terminated_at_succ_n : s.terminated_at (n + 1)) : | |
squash_seq s n = s := | |
begin | |
change s.nth (n + 1) = none at terminated_at_succ_n, | |
cases s_nth_eq : (s.nth n); | |
simp only [*, squash_seq] | |
end | |
/-- If the sequence has not terminated before position `n + 1`, the value at `n + 1` gets | |
squashed into position `n`. -/ | |
lemma squash_seq_nth_of_not_terminated {gp_n gp_succ_n : pair K} | |
(s_nth_eq : s.nth n = some gp_n) (s_succ_nth_eq : s.nth (n + 1) = some gp_succ_n) : | |
(squash_seq s n).nth n = some ⟨gp_n.a, gp_n.b + gp_succ_n.a / gp_succ_n.b⟩ := | |
by simp [*, squash_seq, (seq.zip_with_nth_some (seq.nats_nth n) s_nth_eq _)] | |
/-- The values before the squashed position stay the same. -/ | |
lemma squash_seq_nth_of_lt {m : ℕ} (m_lt_n : m < n) : (squash_seq s n).nth m = s.nth m := | |
begin | |
cases s_succ_nth_eq : s.nth (n + 1), | |
case option.none { rw (squash_seq_eq_self_of_terminated s_succ_nth_eq) }, | |
case option.some | |
{ obtain ⟨gp_n, s_nth_eq⟩ : ∃ gp_n, s.nth n = some gp_n, from | |
s.ge_stable n.le_succ s_succ_nth_eq, | |
obtain ⟨gp_m, s_mth_eq⟩ : ∃ gp_m, s.nth m = some gp_m, from | |
s.ge_stable (le_of_lt m_lt_n) s_nth_eq, | |
simp [*, squash_seq, (seq.zip_with_nth_some (seq.nats_nth m) s_mth_eq _), | |
(ne_of_lt m_lt_n)] } | |
end | |
/-- Squashing at position `n + 1` and taking the tail is the same as squashing the tail of the | |
sequence at position `n`. -/ | |
lemma squash_seq_succ_n_tail_eq_squash_seq_tail_n : | |
(squash_seq s (n + 1)).tail = squash_seq s.tail n := | |
begin | |
cases s_succ_succ_nth_eq : s.nth (n + 2) with gp_succ_succ_n, | |
case option.none | |
{ have : squash_seq s (n + 1) = s, from squash_seq_eq_self_of_terminated s_succ_succ_nth_eq, | |
cases s_succ_nth_eq : (s.nth (n + 1)); | |
simp only [squash_seq, seq.nth_tail, s_succ_nth_eq, s_succ_succ_nth_eq] }, | |
case option.some | |
{ obtain ⟨gp_succ_n, s_succ_nth_eq⟩ : ∃ gp_succ_n, s.nth (n + 1) = some gp_succ_n, from | |
s.ge_stable (n + 1).le_succ s_succ_succ_nth_eq, | |
-- apply extensionality with `m` and continue by cases `m = n`. | |
ext m, | |
cases decidable.em (m = n) with m_eq_n m_ne_n, | |
{ have : s.tail.nth n = some gp_succ_n, from (s.nth_tail n).trans s_succ_nth_eq, | |
simp [*, squash_seq, seq.nth_tail, (seq.zip_with_nth_some (seq.nats_nth n) this), | |
(seq.zip_with_nth_some (seq.nats_nth (n + 1)) s_succ_nth_eq)] }, | |
{ have : s.tail.nth m = s.nth (m + 1), from s.nth_tail m, | |
cases s_succ_mth_eq : s.nth (m + 1), | |
all_goals { have s_tail_mth_eq, from this.trans s_succ_mth_eq }, | |
{ simp only [*, squash_seq, seq.nth_tail, (seq.zip_with_nth_none' s_succ_mth_eq), | |
(seq.zip_with_nth_none' s_tail_mth_eq)] }, | |
{ simp [*, squash_seq, seq.nth_tail, | |
(seq.zip_with_nth_some (seq.nats_nth (m + 1)) s_succ_mth_eq), | |
(seq.zip_with_nth_some (seq.nats_nth m) s_tail_mth_eq)] } } } | |
end | |
/-- The auxiliary function `convergents'_aux` returns the same value for a sequence and the | |
corresponding squashed sequence at the squashed position. -/ | |
lemma succ_succ_nth_convergent'_aux_eq_succ_nth_convergent'_aux_squash_seq : | |
convergents'_aux s (n + 2) = convergents'_aux (squash_seq s n) (n + 1) := | |
begin | |
cases s_succ_nth_eq : (s.nth $ n + 1) with gp_succ_n, | |
case option.none | |
{ rw [(squash_seq_eq_self_of_terminated s_succ_nth_eq), | |
(convergents'_aux_stable_step_of_terminated s_succ_nth_eq)] }, | |
case option.some | |
{ induction n with m IH generalizing s gp_succ_n, | |
case nat.zero | |
{ obtain ⟨gp_head, s_head_eq⟩ : ∃ gp_head, s.head = some gp_head, from | |
s.ge_stable zero_le_one s_succ_nth_eq, | |
have : (squash_seq s 0).head = some ⟨gp_head.a, gp_head.b + gp_succ_n.a / gp_succ_n.b⟩, | |
from squash_seq_nth_of_not_terminated s_head_eq s_succ_nth_eq, | |
simp [*, convergents'_aux, seq.head, seq.nth_tail] }, | |
case nat.succ | |
{ obtain ⟨gp_head, s_head_eq⟩ : ∃ gp_head, s.head = some gp_head, from | |
s.ge_stable (m + 2).zero_le s_succ_nth_eq, | |
suffices : gp_head.a / (gp_head.b + convergents'_aux s.tail (m + 2)) | |
= convergents'_aux (squash_seq s (m + 1)) (m + 2), by | |
simpa only [convergents'_aux, s_head_eq], | |
have : convergents'_aux s.tail (m + 2) = convergents'_aux (squash_seq s.tail m) (m + 1), by | |
{ refine (IH gp_succ_n _), | |
simpa [seq.nth_tail] using s_succ_nth_eq }, | |
have : (squash_seq s (m + 1)).head = some gp_head, from | |
(squash_seq_nth_of_lt m.succ_pos).trans s_head_eq, | |
simp only [*, convergents'_aux, squash_seq_succ_n_tail_eq_squash_seq_tail_n] } } | |
end | |
/-! Let us now lift the squashing operation to gcfs. -/ | |
/-- | |
Given a gcf `g = [h; (a₀, bₒ), (a₁, b₁), ...]`, we have | |
- `squash_nth.gcf g 0 = [h + a₀ / b₀); (a₀, bₒ), ...]`, | |
- `squash_nth.gcf g (n + 1) = ⟨g.h, squash_seq g.s n⟩` | |
-/ | |
def squash_gcf (g : generalized_continued_fraction K) : ℕ → generalized_continued_fraction K | |
| 0 := match g.s.nth 0 with | |
| none := g | |
| some gp := ⟨g.h + gp.a / gp.b, g.s⟩ | |
end | |
| (n + 1) := ⟨g.h, squash_seq g.s n⟩ | |
/-! Again, we derive some simple lemmas that are not really of interest. This time for the | |
squashed gcf. -/ | |
/-- If the gcf already terminated at position `n`, nothing gets squashed. -/ | |
lemma squash_gcf_eq_self_of_terminated (terminated_at_n : terminated_at g n) : | |
squash_gcf g n = g := | |
begin | |
cases n, | |
case nat.zero | |
{ change g.s.nth 0 = none at terminated_at_n, | |
simp only [convergents', squash_gcf, convergents'_aux, terminated_at_n] }, | |
case nat.succ | |
{ cases g, simp [(squash_seq_eq_self_of_terminated terminated_at_n), squash_gcf] } | |
end | |
/-- The values before the squashed position stay the same. -/ | |
lemma squash_gcf_nth_of_lt {m : ℕ} (m_lt_n : m < n) : | |
(squash_gcf g (n + 1)).s.nth m = g.s.nth m := | |
by simp only [squash_gcf, (squash_seq_nth_of_lt m_lt_n)] | |
/-- `convergents'` returns the same value for a gcf and the corresponding squashed gcf at the | |
squashed position. -/ | |
lemma succ_nth_convergent'_eq_squash_gcf_nth_convergent' : | |
g.convergents' (n + 1) = (squash_gcf g n).convergents' n := | |
begin | |
cases n, | |
case nat.zero | |
{ cases g_s_head_eq : (g.s.nth 0); | |
simp [g_s_head_eq, squash_gcf, convergents', convergents'_aux, seq.head] }, | |
case nat.succ | |
{ simp only [succ_succ_nth_convergent'_aux_eq_succ_nth_convergent'_aux_squash_seq, | |
convergents', squash_gcf] } | |
end | |
/-- The auxiliary continuants before the squashed position stay the same. -/ | |
lemma continuants_aux_eq_continuants_aux_squash_gcf_of_le {m : ℕ} : | |
m ≤ n → continuants_aux g m = (squash_gcf g n).continuants_aux m := | |
nat.strong_induction_on m | |
(begin | |
clear m, | |
assume m IH m_le_n, | |
cases m with m', | |
{ refl }, | |
{ cases n with n', | |
{ exact (m'.not_succ_le_zero m_le_n).elim }, -- 1 ≰ 0 | |
{ cases m' with m'', | |
{ refl }, | |
{ -- get some inequalities to instantiate the IH for m'' and m'' + 1 | |
have m'_lt_n : m'' + 1 < n' + 1 := m_le_n, | |
have succ_m''th_conts_aux_eq := IH (m'' + 1) (lt_add_one (m'' + 1)) m'_lt_n.le, | |
have : m'' < m'' + 2 := lt_add_of_pos_right m'' zero_lt_two, | |
have m''th_conts_aux_eq := IH m'' this (le_trans this.le m_le_n), | |
have : (squash_gcf g (n' + 1)).s.nth m'' = g.s.nth m'', from | |
squash_gcf_nth_of_lt (nat.succ_lt_succ_iff.mp m'_lt_n), | |
simp [continuants_aux, succ_m''th_conts_aux_eq, m''th_conts_aux_eq, this] } } } | |
end) | |
end with_division_ring | |
/-- The convergents coincide in the expected way at the squashed position if the partial denominator | |
at the squashed position is not zero. -/ | |
lemma succ_nth_convergent_eq_squash_gcf_nth_convergent [field K] | |
(nth_part_denom_ne_zero : ∀ {b : K}, g.partial_denominators.nth n = some b → b ≠ 0) : | |
g.convergents (n + 1) = (squash_gcf g n).convergents n := | |
begin | |
cases decidable.em (g.terminated_at n) with terminated_at_n not_terminated_at_n, | |
{ have : squash_gcf g n = g, from squash_gcf_eq_self_of_terminated terminated_at_n, | |
simp only [this, (convergents_stable_of_terminated n.le_succ terminated_at_n)] }, | |
{ obtain ⟨⟨a, b⟩, s_nth_eq⟩ : ∃ gp_n, g.s.nth n = some gp_n, from | |
option.ne_none_iff_exists'.mp not_terminated_at_n, | |
have b_ne_zero : b ≠ 0, from nth_part_denom_ne_zero (part_denom_eq_s_b s_nth_eq), | |
cases n with n', | |
case nat.zero | |
{ suffices : (b * g.h + a) / b = g.h + a / b, by | |
simpa [squash_gcf, s_nth_eq, convergent_eq_conts_a_div_conts_b, | |
(continuants_recurrence_aux s_nth_eq zeroth_continuant_aux_eq_one_zero | |
first_continuant_aux_eq_h_one)], | |
calc | |
(b * g.h + a) / b = b * g.h / b + a / b : by ring -- requires `field`, not `division_ring` | |
... = g.h + a / b : by rw (mul_div_cancel_left _ b_ne_zero) }, | |
case nat.succ | |
{ obtain ⟨⟨pa, pb⟩, s_n'th_eq⟩ : ∃ gp_n', g.s.nth n' = some gp_n' := | |
g.s.ge_stable n'.le_succ s_nth_eq, | |
-- Notations | |
let g' := squash_gcf g (n' + 1), | |
set pred_conts := g.continuants_aux (n' + 1) with succ_n'th_conts_aux_eq, | |
set ppred_conts := g.continuants_aux n' with n'th_conts_aux_eq, | |
let pA := pred_conts.a, let pB := pred_conts.b, | |
let ppA := ppred_conts.a, let ppB := ppred_conts.b, | |
set pred_conts' := g'.continuants_aux (n' + 1) with succ_n'th_conts_aux_eq', | |
set ppred_conts' := g'.continuants_aux n' with n'th_conts_aux_eq', | |
let pA' := pred_conts'.a, let pB' := pred_conts'.b, let ppA' := ppred_conts'.a, | |
let ppB' := ppred_conts'.b, | |
-- first compute the convergent of the squashed gcf | |
have : g'.convergents (n' + 1) | |
= ((pb + a / b) * pA' + pa * ppA') / ((pb + a / b) * pB' + pa * ppB'), | |
{ have : g'.s.nth n' = some ⟨pa, pb + a / b⟩ := | |
squash_seq_nth_of_not_terminated s_n'th_eq s_nth_eq, | |
rw [convergent_eq_conts_a_div_conts_b, | |
continuants_recurrence_aux this n'th_conts_aux_eq'.symm succ_n'th_conts_aux_eq'.symm], }, | |
rw this, | |
-- then compute the convergent of the original gcf by recursively unfolding the continuants | |
-- computation twice | |
have : g.convergents (n' + 2) | |
= (b * (pb * pA + pa * ppA) + a * pA) / (b * (pb * pB + pa * ppB) + a * pB), | |
{ -- use the recurrence once | |
have : g.continuants_aux (n' + 2) = ⟨pb * pA + pa * ppA, pb * pB + pa * ppB⟩ := | |
continuants_aux_recurrence s_n'th_eq n'th_conts_aux_eq.symm succ_n'th_conts_aux_eq.symm, | |
-- and a second time | |
rw [convergent_eq_conts_a_div_conts_b, | |
continuants_recurrence_aux s_nth_eq succ_n'th_conts_aux_eq.symm this] }, | |
rw this, | |
suffices : ((pb + a / b) * pA + pa * ppA) / ((pb + a / b) * pB + pa * ppB) | |
= (b * (pb * pA + pa * ppA) + a * pA) / (b * (pb * pB + pa * ppB) + a * pB), | |
{ obtain ⟨eq1, eq2, eq3, eq4⟩ : pA' = pA ∧ pB' = pB ∧ ppA' = ppA ∧ ppB' = ppB, | |
{ simp [*, (continuants_aux_eq_continuants_aux_squash_gcf_of_le $ le_refl $ n' + 1).symm, | |
(continuants_aux_eq_continuants_aux_squash_gcf_of_le n'.le_succ).symm] }, | |
symmetry, | |
simpa only [eq1, eq2, eq3, eq4, mul_div_cancel _ b_ne_zero] }, | |
field_simp, | |
congr' 1; ring } } | |
end | |
end squash | |
/-- Shows that the recurrence relation (`convergents`) and direct evaluation (`convergents'`) of the | |
gcf coincide at position `n` if the sequence of fractions contains strictly positive values only. | |
Requiring positivity of all values is just one possible condition to obtain this result. | |
For example, the dual - sequences with strictly negative values only - would also work. | |
In practice, one most commonly deals with (regular) continued fractions, which satisfy the | |
positivity criterion required here. The analogous result for them | |
(see `continued_fractions.convergents_eq_convergents`) hence follows directly from this theorem. | |
-/ | |
theorem convergents_eq_convergents' [linear_ordered_field K] | |
(s_pos : ∀ {gp : pair K} {m : ℕ}, m < n → g.s.nth m = some gp → 0 < gp.a ∧ 0 < gp.b) : | |
g.convergents n = g.convergents' n := | |
begin | |
induction n with n IH generalizing g, | |
case nat.zero { simp }, | |
case nat.succ | |
{ let g' := squash_gcf g n, -- first replace the rhs with the squashed computation | |
suffices : g.convergents (n + 1) = g'.convergents' n, by | |
rwa [succ_nth_convergent'_eq_squash_gcf_nth_convergent'], | |
cases decidable.em (terminated_at g n) with terminated_at_n not_terminated_at_n, | |
{ have g'_eq_g : g' = g, from squash_gcf_eq_self_of_terminated terminated_at_n, | |
rw [(convergents_stable_of_terminated n.le_succ terminated_at_n), g'_eq_g, (IH _)], | |
assume _ _ m_lt_n s_mth_eq, exact (s_pos (nat.lt.step m_lt_n) s_mth_eq) }, | |
{ suffices : g.convergents (n + 1) = g'.convergents n, by -- invoke the IH for the squashed gcf | |
{ rwa ← IH, | |
assume gp' m m_lt_n s_mth_eq', | |
-- case distinction on m + 1 = n or m + 1 < n | |
cases m_lt_n with n succ_m_lt_n, | |
{ -- the difficult case at the squashed position: we first obtain the values from | |
-- the sequence | |
obtain ⟨gp_succ_m, s_succ_mth_eq⟩ : ∃ gp_succ_m, g.s.nth (m + 1) = some gp_succ_m, from | |
option.ne_none_iff_exists'.mp not_terminated_at_n, | |
obtain ⟨gp_m, mth_s_eq⟩ : ∃ gp_m, g.s.nth m = some gp_m, from | |
g.s.ge_stable m.le_succ s_succ_mth_eq, | |
-- we then plug them into the recurrence | |
suffices : 0 < gp_m.a ∧ 0 < gp_m.b + gp_succ_m.a / gp_succ_m.b, by | |
{ have ot : g'.s.nth m = some ⟨gp_m.a, gp_m.b + gp_succ_m.a / gp_succ_m.b⟩, from | |
squash_seq_nth_of_not_terminated mth_s_eq s_succ_mth_eq, | |
have : gp' = ⟨gp_m.a, gp_m.b + gp_succ_m.a / gp_succ_m.b⟩, by cc, | |
rwa this }, | |
refine ⟨(s_pos (nat.lt.step m_lt_n) mth_s_eq).left, _⟩, | |
refine add_pos (s_pos (nat.lt.step m_lt_n) mth_s_eq).right _, | |
have : 0 < gp_succ_m.a ∧ 0 < gp_succ_m.b := s_pos (lt_add_one $ m + 1) s_succ_mth_eq, | |
exact (div_pos this.left this.right) }, | |
{ -- the easy case: before the squashed position, nothing changes | |
refine s_pos (nat.lt.step $ nat.lt.step succ_m_lt_n) _, | |
exact eq.trans (squash_gcf_nth_of_lt succ_m_lt_n).symm s_mth_eq' } }, | |
-- now the result follows from the fact that the convergents coincide at the squashed position | |
-- as established in `succ_nth_convergent_eq_squash_gcf_nth_convergent`. | |
have : ∀ ⦃b⦄, g.partial_denominators.nth n = some b → b ≠ 0, by | |
{ assume b nth_part_denom_eq, | |
obtain ⟨gp, s_nth_eq, ⟨refl⟩⟩ : ∃ gp, g.s.nth n = some gp ∧ gp.b = b, from | |
exists_s_b_of_part_denom nth_part_denom_eq, | |
exact (ne_of_lt (s_pos (lt_add_one n) s_nth_eq).right).symm }, | |
exact succ_nth_convergent_eq_squash_gcf_nth_convergent this } } | |
end | |
end generalized_continued_fraction | |
open generalized_continued_fraction | |
namespace continued_fraction | |
/-- Shows that the recurrence relation (`convergents`) and direct evaluation (`convergents'`) of a | |
(regular) continued fraction coincide. -/ | |
theorem convergents_eq_convergents' [linear_ordered_field K] {c : continued_fraction K} : | |
(↑c : generalized_continued_fraction K).convergents = | |
(↑c : generalized_continued_fraction K).convergents' := | |
begin | |
ext n, | |
apply convergents_eq_convergents', | |
assume gp m m_lt_n s_nth_eq, | |
exact ⟨zero_lt_one.trans_le ((c : simple_continued_fraction K).property m gp.a | |
(part_num_eq_s_a s_nth_eq)).symm.le, | |
c.property m gp.b $ part_denom_eq_s_b s_nth_eq⟩ | |
end | |
end continued_fraction | |